Interactive motion-controlled games in the neurorehabilitation of adult post-stroke patients - Mikołajewska, Emilia; Mikołajewski, Dariusz (Journal of Education, Health and Sport, 2015)
Mikołajewska Emilia, Mikołajewski Dariusz. Interactive motion-controlled games in the neurorehabilitation of adult post-stroke patients. Journal of Education, Health and Sport. 2015;5(8):311-317. ISSN 2391-8306. DOI 10.5281/zenodo.28856 http://dx.doi.org/10.5281/zenodo.28856 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A311-317 https://pbn.nauka.gov.pl/works/611577 POL-index https://pbn.nauka.gov.pl/polindex/browse/article/article-8153ebff-7978-415b-bb64-bd4f39919506 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.07.2015. Revised 21.08.2015. Accepted: 21.08.2015. Interactive motion-controlled games in the neurorehabilitation of adult post-stroke patients Emilia Mikołajewska1,2,3, Dariusz Mikołajewski3,4,5 1 Department of Physiotherapy, Ludwik Rydygier Collegium Medium in Bydgoszcz, Nicolaus Copernicus University in Toruń, Poland 2 Rehabilitation Clinic, The 10th Clinical Military Hospital with Policlinic, Bydgoszcz, Poland 3 Neurocognitive Laboratory, Interdisciplinary Center for Modern Technologies, Nicolaus Copernicus University in Toruń, Poland 4 Institute of Mechanics and Applied Computer Sciences, Kazimierz Wielki University, Bydgoszcz, Poland 5 Department of Informatics, Nicolaus Copernicus University, Toruń, Poland Corresponding author: Emilia Mikołajewska Rehabilitation Clinic Military Clinical Hospital No. 10 and Polyclinic Bydgoszcz, Poland e-mail: e.mikolajewska@wp.pl, emiliam@cm.umk.pl www: http://emikolajewska.netstrefa.eu Keywords: neurorehabilitation; physiotherapy; stroke; neurological deficit; therapeutic game. Abstract Despite efforts of scientists and clinicians stroke still constitutes one of the major causes of disability worldwide. Motion-controlled video games become increasingly common adjunct to the traditional physical therapy. Such games are usually available, low-cost, fun, and functional ways to increase everyday treatment possibilities, both in hospital, ambulatory and home settings. Research and scientific publications concerning this issue are still rare. Assessment how interactive motion-controlled games can be incorporated into current guidelines of the eclectic approach within neurorehabilitation of adult post-stroke survivors is key issue within contemporary neurorehabilitation of adults. Complementary use of such games may constitute another breakthrough both in in-patient and out-patient rehabilitation and care. This review aims at potential of aforementioned solutions and modalities for the rehabilitation of function in cases of stroke.